2017
DOI: 10.1186/s12887-017-0823-y
|View full text |Cite
|
Sign up to set email alerts
|

Social inclusion for children with hearing loss in listening and spoken Language early intervention: an exploratory study

Abstract: BackgroundSocial inclusion is a common focus of listening and spoken language (LSL) early intervention for children with hearing loss. This exploratory study compared the social inclusion of young children with hearing loss educated using a listening and spoken language approach with population data.MethodsA framework for understanding the scope of social inclusion is presented in the Background. This framework guided the use of a shortened, modified version of the Longitudinal Study of Australian Children (LS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
5
1
2
Order By: Relevance
“…In contrast to our expectations, the receptive and expressive language scores of 4-year-old children with HL did not clinically contribute to the development of QoL. The absence of a clear relation between language skills and QoL in children with HL was also found in other studies on language skills and social emotional functioning [12,[63][64][65][66]. They found that communication skills and not language skills are more import for social functioning which in turn can affect the wellbeing of children with HL.…”
Section: Changes In Qol Over Timecontrasting
confidence: 99%
“…In contrast to our expectations, the receptive and expressive language scores of 4-year-old children with HL did not clinically contribute to the development of QoL. The absence of a clear relation between language skills and QoL in children with HL was also found in other studies on language skills and social emotional functioning [12,[63][64][65][66]. They found that communication skills and not language skills are more import for social functioning which in turn can affect the wellbeing of children with HL.…”
Section: Changes In Qol Over Timecontrasting
confidence: 99%
“…Relying on factors such as 'education' and 'Interacting with society and fulfilling social roles', they found that social inclusion was influenced by speech abilities and vocabulary. Constantinescu-Sharpe et al (2017) examined two aspects of social Inclusion, namely 'education' and 'interacting with society and fulfilling social goals'. They surveyed the parents of deaf children order categorical Interactions among school and background characteristics.…”
Section:  the Bilingual-bicultural Approachmentioning
confidence: 99%
“…The DHH people are not able to fully participate in the hearing world due to the communication barrier they have with hearing people, and the lack of equal access to information that hearing people enjoy. This deprivation of information causes detrimental impacts on self-confidence and self-concept for deaf communities (Constantinescu-Sharpe et al, 2017). Consequently, it causes delays in educational, social and psycho-social development within deaf communities, and negatively impacts their opportunities in employment, education and income (McKee et al, 2012;Greenberg and Kusché, 1993).…”
Section: Introductionmentioning
confidence: 99%